Boundaries around Group Interaction The Effect of Size and Status - Knowles, Eric S.; Wisconsin Univ., Green Bay. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
The stimulus value of group boundaries was investigated in a field experiment. It was hypothesized that the size of a group and the status of its members would reduce the permeability of a boundary around an interacting group. Two or 4 interacting people of high or low status interrupted the traffic flow in a university hallway. Results indicate support for the hypothesis: fewer passersby walked through high status than low status groups. A control condition where wastebarrels replaced the interactors was penetrated more than either high or low status interacting groups. The author sees, in these results, support for Lyman and Scott's hypothesis that groups develop territorial boundaries, and for Milgram and Toch's hypothesis that group boundaries vary in their permeability. (Author/TL)
Availability: Eric S. Knowles, College of Community Sciences, University of Wisconsin-Green Bay, Green Bay, Wisconsin 54302.
ERIC Note: Paper presented at the meetings of the Eastern Psychological Association, New York, New York, April 15-17, 1971.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavior; Behavior Patterns; Group Behavior; Group Dynamics; Group Status; Group Structure; Group Unity; Groups